2018
DOI: 10.1186/s13071-018-3179-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic insights into the early host-pathogen interaction of cat intestine with Toxoplasma gondii

Abstract: BackgroundAlthough sexual reproduction of the parasite Toxoplasma gondii exclusively occurs in the cat intestine, knowledge about the alteration of gene expression in the intestine of cats infected with T. gondii is still limited. Here, we investigated the temporal transcriptional changes that occur in the cat intestine during T. gondii infection.MethodsCats were infected with 100 T. gondii cysts and their intestines were collected at 6, 12, 18, 24, 72 and 96 hours post-infection (hpi). RNA sequencing (RNA-Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…Previous studies on host transcriptomics have revealed a general host-pathogen interaction in an in vitro T. gondii infection model [41] and in cat intestine [42]. To our knowledge, our study provides the first single cell transcriptomic investigation of dendritic cell Bcl3 in an experimental murine model of Toxoplasmosis.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies on host transcriptomics have revealed a general host-pathogen interaction in an in vitro T. gondii infection model [41] and in cat intestine [42]. To our knowledge, our study provides the first single cell transcriptomic investigation of dendritic cell Bcl3 in an experimental murine model of Toxoplasmosis.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies using transcriptome sequencing detected many DEGs in T. gondii -infected animal models [ 31 33 ]. These DEGs were mainly involved in immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with that reported previously (Weinert et al 2011 ; Zhou et al 2016a ). T. gondii infection can alter the expression of genes involved in protein modification processes in feline small intestine (Cong et al 2018 ; Wang et al 2018 ). Thus, it is possible that the lack of clear acetylation motif in this study could be due to alteration in the genes participating in ubiquitous acetylation process by T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%